Influence of Capillary Pressure on CBM Reservoir Development Effect - JIA Huimin, YAN Ling, MAO Chonghao, ZHANG Qing, ZHANG Guangbo, FAN Bin (Meikuang Anquan, 2020)
To research the effects of capillary pressure of coalbed methane reservoir on the development of coalbed methane, this paper, based on wettability experiments and field production data, proposes the seal mechanism and types by capillary pressure of coalbed methane formation, and then proposes three types of coalbed methane reservoirs and their typical production curves. The results show that the wettability of coal and rock is water wet and capillary pressure is resistance in the process of coalbed methane production. After the methane is generated, it is adsorbed on the pore surface of coal under the influence of capillary pressure and reservoir hydrostatic pressure. When the gas pressure in the pore is less than the breakthrough pressure, the gas is closed in the pore. According to the difference of gas-sealing type of capillary pressure, coalbed methane reservoir can be divided into three types: capillary pressure trapping type, under-saturated type and saturated type. The capillary pressure of capillary trapping type reservoir is greater than the gas pressure in the pores. Continuous drainage cannot overcome the capillary pressure, and the development effect is the worst. The gas pressure in the pores of the unsaturated reservoir is greater than the capillary pressure, and the static water pressure can be reduced by continuous drainage, making the gas continuously produced, and the development performance is relatively good. The gas pressure in the pores of saturated reservoirs is greater than the gas breakthrough pressure, and methane gas can be produced without drainage and depressurization, so high and stable production can be achieved.